Growth Pattern and Sex Ratio of Octopus vulgaris at Bone Gulf - Amir, Faisal; Mallawa, Achmar; Umar, Moch. Tauhid (Agrikan Jurnal Agribisnis Perikanan, 2021)
Octopus vulgaris in the Bone gulf waters was caught with modified fishing rods resembling crabs, caught throughout the year with the peak fishing season in the west season (January to March) with a small population without any management regulation. The purpose of this study was to obtain information on growth patterns, condition factors, and sex ratio of O. vulgaris in the Bone gulf waters. The method used is a survey method. The sample measurements were carried out at the largest collector domiciled on Kambuno Island, Sinjai Regency, South Sulawesi Province from May to August 2021. The measurements of dorsal mantle length (MLd:cm), body weight (g) and sex determination were carried out directly in the field. The results showed that the dorsal mantle length of O. vulgaris ranged from 7.0 cm – 20.0 cmDML (13.7±2.3 cmDML) with a weight between 50 g - 3270 g (1076.4±522.5 g) for males and 7.0 cm – 22.0 cmDML (13.0±2.3 cmDML) with a weight between 70 g - 4800 g (1043.8±526.4 g) for females. Negative allometric growth patterns. The sex ratio between males and females is not balanced.